Effective width equations accounting for element interaction for cold-formed stainless steel square and rectangular hollow sections. (June 2015) - Bock, M.; Real, E.
Abstract: Rectangular hollow sections featuring high height-to-width (aspect) ratios have shown to offer improved ultimate capacity due to the effects of the interaction between the elements within the cross-section which are particularly significant for slender cross-sections (Class 4) undergoing local buckling. The European design rules dealing with stainless steel, EN 1993-1-4 [1], utilises the concept of cross-section classification and the effective width method for the design of slender cross-sections susceptible to local buckling neglecting such interaction effects, hence resulting in conservative predictions. This paper examines the benefits of element interaction effects on cold-formed ferritic stainless steel compressed sections on the basis of carefully validated finite element models. Following parametric studies, the applicability of various alternative design approaches accounting for element interaction to ferritic stainless steel is assessed and effective width curves, as well as a Class 3 limiting slenderness equation, are derived herein as an explicit function of the aspect ratio. Comparisons with the loads achieved in the FE models have shown that the proposed effective width equations allowing for the benefits of element interaction improve capacity predictions making design more cost-effective. Highlights: Numerical modelling of cold-formed ferritic stainless steel stub columns Study of the influence of some key parameters on the numerical response Successful validation of the scope of various methods to cover ferritic steel Incorporation of element interaction effects into the effective width formulation Reliability analysis and validation of the proposed method against existing tests